Elder Voices: Wisdom about Indigenous Peoples' Food Systems from the Holders of Knowledge. (17th May 2021) - Flanagan, Hope; Frizzell, Linda B; Kassi, Norma; Nuvayestewa, Leon; Warne, Beverly S; Kurzer, Mindy S
ABSTRACT: This compilation includes the stories of 5 Native American and First Nation elders, in which they share their wisdom, experience, and opinions on Indigenous food systems and health. Each of these elders participated in the Fourth Annual Conference on Native American Nutrition, held in September 2019 at Mystic Lake Center on land of the Shakopee Mdewakanton Sioux Community in Prior Lake, Minnesota. Abstract : This is a commentary in which 5 Indigenous elders share their wisdom, experience, and opinions on Indigenous food systems and health.